Mathematical model of adjustment stretching shoe leather material with mineral filling - Козарь, Оксана Петрівна; Коновал, Віктор Павлович; Wozniak, Boguslaw; Оленіч, Андрій Васильович (Eastern-European Journal of Enterprise Technologies, 2014)
Shoe shape stability is one of the most important indicators of quality which depends primarily on the deformation properties of the skin, its stretching. It is possible to increase shoe shape stability using the technological process of adjustment operations of stretching the skin to optimal values , which are necessary for the production of high quality footwear. Ductility index influences the percentage of leather waste in the performance of recover and last operations , i.e. material resource saving and cost of shoes. We present a mathematical model of stretching adjustment of the skin with mineral content to accurately calculate the area of parts of the work piece in this paper. The proposed concept of stretching adjustment method involves iterative process of skins preliminary tensile elongation with fixation of each cycle. The physical model of the process has been built, including hydration operations, stretching, drying in a stretched state and relieve of tension. By means of mathematical analysis and the theory of sets, the dependence of the residual elongation size of the researched skins on the degree of hydration of the skin, stretching the size and number of repeated stretching has been found. Implementation of the correction stretching process of shoe leather will reduce the material and energy resources while improving the competitiveness of shoes.